Beef Salt-Soluble Proteins and Seaweed (Eucheuma cottonii) Flour Interactions to the Quality of Heat-Induced Gel Matrix Development (Faculty of Animal Science Universitas Brawijaya, 2020)
The objective of this study was to observe the interactions between salt-soluble proteins from beef and seaweed (Eucheuma cottonii) flour and its effect to the quality of the produced protein gel. The study was conducted as experimental research with two factorials completely randomized design. The effect of different NaCl (2.0%; 2.5%; 3.0%; and 3.5%) and Eucheuma cottonii flour (5%; 10%; and 15%) concentrations was observed to the physical and proximate quality of the protein gel matrix. The observed gel quality variables include pH, gel strength, color (L, a*, and b*), moisture, protein, and fat content. The gel was gelatinized at 90Â°C for 20 min and cooled down at 4Â°C for 12 h. The results showed that there was no interaction effect found on all of observed variables. However, a highly significant effect (P<0.01) was found on the ash content with different salt concentrations, while different Eucheuma cottonii flour concentrations improved the gel strength (P<0.01) and significantly gave darker (P<0.01) color. The effect of Eucheuma cottonii flour on the physicochemical properties of the gel was concentration dependent. Therefore, this study concludes that Eucheuma cottonii flour showed a potential as binding or filling agent to form strong gel matrix in processed meat products.